Practical Strategies for Sustaining Motivation in Foreign Language Learning (Eurasian Scientific Herald, 2024)
This article aims to explore practical ideas and strategies for sustaining motivation in the process of learning foreign languages. Language learning motivation plays a crucial role in learners' progress and overall success. However, sustaining motivation can be challenging, particularly in long-term language learning endeavors. This article reviews current research literature and provides practical recommendations to help learners maintain their motivation throughout their language-learning journey. The strategies discussed encompass goal setting, relevance, enjoyment, study routines, varied learning resources, community engagement, progress tracking, embracing mistakes, rewards, and maintaining a positive mindset. By implementing these practical ideas, language learners can enhance their motivation levels and effectively sustain their language learning momentum